Refugee entrepreneurship motivations in Sweden and Germany: a comparative case study - Ghazal Zalkat; Henrik Barth; Lubna Rashid (Small Business Economics, 2023)
Refugee entrepreneurs can make a significant contribution to sustainable growth and development in host countries. However, comprehensive comparative studies of refugee entrepreneurial motivations are scarce, particularly in the absence of a theoretical framework on entrepreneurship motivation that is suitable for such contexts. This is a research topic that is increasingly of interest to scholars and policymakers working with refugee workforce integration, particularly in light of forecasted increases in global forced displacement over the next years. This paper tests and extends newly constructed entrepreneurship motivation measures, comparing person-related factors and the perceptions of environmental-related factors for Syrian refugee entrepreneurs in Sweden and Germany. The results indicate that their motivations differ between the two countries with respect to market conditions, the educational environment, dissatisfaction, and know-how. However, refugee entrepreneurs in both countries have similar levels of entrepreneurial ambition and attitude and are motivated by similar perceptions of social environments and cultural norms. This paper identifies how entrepreneurship motivation differences could be considered by governments to better shape and inform host countries' programs and policies to improve refugee entrepreneurship and subsequent integration.
Keywords: L26; D91; M13; F22; J15; J24; O57; 330; Refugee entrepreneurship; Entrepreneurial motivation; Migration; Socioeconomic integration; Sweden; Germany